Biomarkers in Asthma - Interpretation, and Utility in Current Asthma Management - Leru, Polliana M. (Current Respiratory Medicine Reviews, 2021)
Asthma is a complex and highly heterogeneous disorder, having many clinical phenotypes and underlining mechanisms, a broad spectrum of severity, and variable response to controller therapy. Intensive research has been focused on the identification and validation of the most appropriate biomarkers in the clinical management of asthma, mostly addressed to severe and refractory cases. The use of reliable biomarkers in severe asthma can contribute to a better understanding of disease biology, diagnosis and screening, by a refined characterization of particular phenotypes and endotypes, assessment of severity, control, and prognosis. There is an increasing interest to validate biomarkers able to indicate the adequate therapeutic choice from the class of biological agents, most of them targeting T2 inflammation. Using a reliable and validated biomarker, the clinician can monitor the response to initial therapy and early identify a severe phenotype. The aim of this paper is to review the clinical utility of relevant biomarkers currently used in asthma management. Indication for more advanced and efficient therapy, such as monoclonal antibodies and selection of the optimal molecule, is based on biomarkers and clinical criteria, according to the most recent experts’ recommendations. Peripheral blood eosinophils are considered an important biomarker for the selection and identification of responders to anti-eosinophil biological therapy. Real-life long-term studies to confirm the precise use and cutoffs of the already approved biomarkers for T2 phenotypes and to identify reliable biomarkers for non- T2 severe asthma are still unmet needs in asthma management.
Keywords: Asthma management